Neuronal death resulting from targeted disruption of the Snf2 protein ATRX is mediated by p53. - Seah, C; Levy, M; Jiang, Y; Mokhtarzada, S; Higgs, D; Gibbons, R; Bérubé, N (2008)
ATRX, a chromatin remodeling protein of the Snf2 family, participates in diverse cellular functions including regulation of gene expression and chromosome alignment during mitosis and meiosis. Mutations in the human gene cause alpha thalassemia mental retardation, X-linked (ATR-X) syndrome, a rare disorder characterized by severe cognitive deficits, microcephaly and epileptic seizures. Conditional inactivation of the Atrx gene in the mouse forebrain leads to neonatal lethality and defective neurogenesis manifested by increased cell death and reduced cellularity in the developing neocortex and hippocampus. Here, we show that Atrx-null forebrains do not generate dentate granule cells due to a reduction in precursor cell number and abnormal migration of differentiating granule cells. In addition, fewer GABA-producing interneurons are generated that migrate from the ventral telencephalon to the cortex and hippocampus. Staining for cleaved caspase 3 demonstrated increased apoptosis in both the hippocampal hem and basal telencephalon concurrent with p53 pathway activation. Elimination of the tumor suppressor protein p53 in double knock-out mice rescued cell death in the embryonic telencephalon but only partially ameliorated the Atrx-null phenotypes at birth. Together, these findings show that ATRX deficiency leads to p53-dependent neuronal apoptosis which is responsible for some but not all of the phenotypic consequences of ATRX deficiency in the forebrain.